ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA SISA LEBIH PERHITUNGAN ANGGARAN (SiLPA) TAHUN 2010 DITINJAU DARI ASPEK MANAJEMEN KEUANGAN DAERAH (Studi Pada Pemerintah Provinsi Nusa Tenggara Timur) - , THOMAS TUBA BALI, Prof. Dr. Abdul Halim, M.BA, Akt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, the SiLPA phenomenon is frequently became a hot problem discussed at each end of fiscal year, almost at all regional governments in Indonesia, without known for certain the cause factors. This has impacts on the fallacy in assessments to the regional financial management performance. There is still many parties who do not understand exactly what is the SiLPA, so that in conducting assessments, often obsessed only in the efficiency/inefficiency problem, and focused only in the large/small total number of SiLPA produced. Talking about SiLPA, it is actually a complex problem necessary to be studied in depth firstly in various aspects that can be known for certain what is the cause factor, so it is not mistaken in giving any statement or judgment. This research aims to find out the cause factors the SiLPA occurred, as input to correct the wrong perception on the true SiLPA meaning and disclose the broad insight to know more about SiLPA. In addition, the results of research as input to improve the regional government financial performance in future. Data used in this research is primary data in the questionnaires form as the main data as well as the supporting data in the form of interviews result and official documents released by the Regional Government of NTT. Population of this research is the local financial management apparatures at 24 SKPD in scope of the NTT provincial government that manages the income and expenditure. analysis technique used is Exploratory Factor Analysis (EFA). The results of research known that from the local financial management aspects there are 7 (seven) the cause factors of SiLPA with total variance could be explained reached 66.98% of 62 (sixty-two) indicators used. The seven factors include: (1) Regional Expenditure Management Factor with total variance of 19.68%. (2) Regional Asset Management Factors, with total variance of 13.60%. (3) Regional Revenue Management Factors, with total variance of 10%. (4) Financial Management Reform Factor, with total variance of 8.03%. (5) Partnership Management Factor of Regional Government, with total variance of 6.85%. (6) Cash Management and Budget Factors, with total variance of 4.27%. (2) Loan Management Factors and Regional Investment, with total variance of 3.54%.